Match analyses of table tennis in China: a systematic review - Zhang, H.; Zhou, Z.; Yang, Q. (Journal of Sports Sciences, 2018)
This study is a systematic review of match analyses of table tennis that can be used for reference in China. Using the China National Knowledge Infrastructure (CNKI) as the search tool and "table tennis" as the keyword, we searched for all papers on table tennis published in Chinese core sports journals between 1980 and 2016. Then, we read through 1209 papers and divided them into different categories according to their publication types and main topics. Among them, 128 papers on match analyses met three inclusion criteria, and hence they were chosen as the reviewed studies. The results show that match analyses of table tennis in China have a sound research foundation, with the "three-phase evaluation method" and research on different topics playing an active role in helping coaches and players understand table tennis matches. Computer-aided match analysis not only enhanced the capacity and speed of data processing, but it also facilitated coaches` and players` understanding of tactical features by video feedback and multimedia presentation. Although match analyses of table tennis based on different theories or models are still in a preliminary stage, these studies are indeed pushing the development of this field.